Practical considerations relevant to treatment with the gene therapy beremagene geperpavec-svdt for dystrophic epidermolysis bullosa - Amy S. Paller; Shireen V. Guide; Diego Ayala; Mercedes E. Gonzalez; Anne W. Lucky; Isin Sinem Bagci; M. Peter Marinkovich (Taylor & Francis Group, 2024)
AbstractBackground/purpose Dystrophic epidermolysis bullosa (DEB), a rare genetic skin disease caused by loss-of-function mutations in COL7A1, the gene encoding type VII collagen (COL7), is characterized by skin blistering, scarring, and extracutaneous manifestations that markedly reduce patient quality-of-life. Beremagene geperpavec-svdt ('B-VEC') is a gene therapy employing a non-integrating, replication-defective herpes simplex virus type 1 (HSV-1)-based vector encoding two copies of full-length human COL7A1 to restore COL7 protein after topical administration to DEB wounds. B-VEC was approved in the United States in 2023 as the first topical gene therapy and the first approved treatment for DEB. However, few providers have experience with use of this gene therapy.Methods Data was obtained through literature review and the experience of providers who participated in the B-VEC clinical study or initiated treatment after B-VEC approval.Results This review discusses the burden of disease, describes the clinical trial outcomes of B-VEC, and provides physician and patient/caregiver recommendations as a practical guide for the real-world use of B-VEC, which can be administered in-office or at the patient's home.Conclusions By continuing to optimize the practical aspects of B-VEC administration, the focus will continue to shift to patient-centric considerations and improved patient outcomes.